1999
DOI: 10.1016/s0735-1097(99)00453-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct coronary stenting without predilation

Abstract: Direct stenting without predilation in selected lesions seems to be a safe and successful procedure that provides a way to contain cost and to shorten radiation exposure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 15 publications
8
67
0
2
Order By: Relevance
“…In particular, it has been suggested that direct stenting may help to "tack up" dissection flaps as they form and thereby prevent extension. 5,[11][12][13] In our study, a relatively high incidence of dissection was observed in the conventional stent group (13% versus the direct stent group (2.5%), providing support for this concept. A relatively low incidence of side-branch loss following direct stenting has been reported and it was speculated that this result was due to a reduction in the "snow plow" effect.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In particular, it has been suggested that direct stenting may help to "tack up" dissection flaps as they form and thereby prevent extension. 5,[11][12][13] In our study, a relatively high incidence of dissection was observed in the conventional stent group (13% versus the direct stent group (2.5%), providing support for this concept. A relatively low incidence of side-branch loss following direct stenting has been reported and it was speculated that this result was due to a reduction in the "snow plow" effect.…”
Section: Discussionsupporting
confidence: 54%
“…In animal models, direct stenting appears to result in less endothelial denudation than dilation followed by stenting. 14,15) This has been hypothesized to result in a reduced intimal proliferative response and potentially less restenosis 5,14,15) and, one might also speculate less thrombotic potential, and less future cardiac events. The BET study showed better, but statistically insignificant, results with direct stent implantation concerning the incidence of major adverse cardiac events (5.3% vs 11.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briguori and colleagues performed a retrospective comparison of patients undergoing direct and conventional stenting. 189 Direct stenting was successful in 94% of cases in this single-centre analysis, with no inhospital deaths, MIs or emergency bypass surgery. In the direct stenting group there were significant reductions in procedure time (by 30%), radiation exposure time (by 25%), contrast dye, balloon use and cost.…”
Section: Direct Stenting Compared With Conventional Stentingmentioning
confidence: 67%
“…20) Direct stenting with bare metal stents has been shown to reduce procedural time, radiation exposure time, and costs. 21) This technique may be particularly attractive for implanting drug-eluting stents when considering the increased cost of these devices. Potential damage to the stent polymer is a major source of concern during implantation of drug-eluting stents without predilatation, however, there is evidence demonstrating the safety and feasibility of this technique in drug-eluting stents.…”
Section: Discussionmentioning
confidence: 99%